An alternative to standard nuclear core control using a multi-objective approach. (February 2019) - Lemazurier, L.; Chevrel, P.; Grossetête, A.; Yagoubi, M.
Abstract: This paper proposes an alternative to standard nuclear core control. The control objectives are standard and concern the Average Coolant Temperature, the Axial Offset and the rod bank position (Pbank in this study). They were carefully formalized before proceeding to LTI structured controllers synthesis at various operating points, using a multi-objective approach. This study relies on a point kinetic core model, embedding an AO estimator. A Non-smooth optimization technique is used to solve the control problems at each operating point. Then gain scheduling is performed, taking advantage of the parsimonious parameterization of the considered multivariable controller. Finally, simulations are carried out on a highly realistic reactor model including a Xenon model and show the benefits of the new control Highlights: The controller is a promising alternative to most advanced nuclear core control. The design methodology reduces pessimism compared to actual solutions. The control structure is adaptable so that it can accept new actuators and sensors. The control framework enables to meet explicitly the industrial specifications. The highly complex control problem is solved using non-smooth optimization tools.